Halal Label: The Determinants of Purchase Decision - Aprih Santoso; Nir Setyo Wahdia; M. Hasan Ma'ruf (AMAR (Andalas Management Review), 2021)
This study aims to analyze the effect of the halal label, product quality, financial literacy and price on purchasing decisions for REVLON lipstick products in Semarang. The number of samples in this study were 100 respondents, the sampling technique was purposive sampling. The analytical tool used is path analysis, where previously tested the validity and reliability as well as the classical assumption test. The test results show that the halal label, financial literacy and price have a positive and significant effect on purchasing decisions for REVLON lipstick products in Semarang, while product quality has a negative effect on purchasing decisions. This study uses the halal variable as one of the determinants of purchasing decisions because it is still rarely used by previous marketing research studies with Muslim women as respondents. Research limitations: 1. The object used in this research only focuses on one product. 2. This study only uses 4 (four) independent variables, namely: Halal Label, Product Quality, Financial Literacy and Price. 3. This study only used a limited sample of 100 respondents.